VeraPDF: building an open source, industry supported PDF/A validator for cultural heritage institutions. Issue 2 (8th May 2017) - Wilson, Carl; McGuinness, Rebecca; Jung, Joachim
Abstract : Purpose: This paper describes the development of the veraPDF validator. The objective of veraPDF is to build an industry supported, open source validator for all parts and conformance levels of the PDF/A specification for archival PDF documents. The project is led by the Open Preservation Foundation and the PDF Association and is funded by the EU PREFORMA project. Design/methodology/approach: veraPDF is designed to meet the needs of the digital preservation community and the PDF industry alike. The technology is subject to the review of and acceptance by the PDF Association's PDF Validation Technical Working Group, including many participants of the relevant ISO working groups. Cultural heritage institutions are collecting ever-increasing volumes of digital information, which they have a mandate to preserve for the long term. However, in many cases, they need to ensure their content has been produced to the specifications of a standard file format, as well as any acceptance criteria stated in their institutional policy. Findings: With increasing knowledge and experience of processes and policies, cultural heritage institutions are influencing the production and development of digital preservation software. The product development funded by the PREFORMA project shows how such cooperation can benefit the community as a whole. Originality/value: This paper describes the value of an open source approach to developing a PDF/A validator for cultural heritage organisations.